Production and characterization of biodiesel fuel produced from third-generation feedstock - Verma, Suraj; Sahu, Deepak; Almutairi, Bader O. (Frontiers in Materials, 2024)
Biodiesel is an eco-friendly and renewable alternative fuel, it can be obtained from soybean oil, vegetable oils, animal fat, or micro-algae. This study presents a comprehensive investigation into the production and characterization of microalgae biodiesel utilizing multiple analytical techniques, including CHNSO analysis, Fourier Transform Infrared Spectroscopy (FTIR), Gas Chromatography-Mass Spectrometry (GC-MS), and Proton Nuclear Magnetic Resonance spectroscopy ( 1 H NMR). The CHNSO analysis revealed the elemental composition of biodiesel blends, highlighting the effects of TiO2 nanoparticle concentration on carbon, nitrogen, sulphur, and oxygen content, with increasing TiO2 concentration a steady increase in carbon content and a gradual decrease in nitrogen content were observed. According to the CHNSO analysis, sulfur content of blended biodiesel was found to be lower than that of fossil diesel, with an empirical formula of CH2.26N0.000584S0.000993O0.0517. FTIR and 1 H NMR spectroscopy confirmed the synthesis of biodiesel. Fourier transform infrared resonance confirmed the presence of ester groups at 1732 cm -1 , and a prominent peak at 1455 cm -1 indicated higher carbon content in the blended biodiesel.GC-MS analysis identified compounds of fatty acid methyl ester (FAMEs) and hydrocarbons.The major components of FAMEs were 9-Octadecenoic acid methyl ester (C19H36O2), Linoleic acid ethyl ester (C20H36O2) and Hexadecanic acid methyl ester (C17H34O2), with compositions of 20.65 %, 9.67 %, and 6.26 %, respectively. The presence of methyl ester in the blended fuel suggests its potential as an alternative fuel source.